Endoscopic resection-related colorectal strictures: risk factors, management, and long-term outcomes - Gupta, Sunil; Vosko, Sergei; Shahidi, Neal; O’Sullivan, Timothy; Cronin, Oliver; Whitfield, Anthony; Kurup, Rajiv; Sidhu, Mayenaaz; Lee, Eric Y. T.; Williams, Stephen J.; Burgess, Nicholas G.; Bourke, Michael J. (Endoscopy, 2023)
Introduction Colorectal strictures related to endoscopic resection (ER) of large nonpedunculated colorectal polyps (LNPCPs) may be problematic. Data on prevalence, risk factors, and management are limited. We report a prospective study of colorectal strictures following ER and describe our approach to management.Methods We analyzed prospectively collected data over 150 months, until June 2021, for patients who underwent ER for LNPCPs ≥ 40 mm. The ER defect size was graded as < 60 %, 60 %–89 %, or ≥ 90 % of the luminal circumference. Strictures were considered “severe” if patients experienced obstructive symptoms, “moderate” if an adult colonoscope could not pass the stenosis, or “mild” if there was resistance on successful passage. Primary outcomes included stricture prevalence, risk factors, and management.Results 916 LNPCPs ≥ 40 mm in 916 patients were included (median age 69 years, interquartile range 61–76 years, male sex 484 [52.8 %]). The primary resection modality was endoscopic mucosal resection in 859 (93.8 %). Risk of stricture formation with an ER defect ≥ 90 %, 60 %–89 %, and < 60 % was 74.2 % (23/31), 25.0 % (22/88), and 0.8 % (6 /797), respectively. Severe strictures only occurred with ER defects ≥ 90 % (22.6 %, 7/31). Defects < 60 % conferred low risk of only mild strictures (0.8 %, 6/797). Severe strictures required earlier (median 0.9 vs. 4.9 months; P = 0.01) and more frequent (median 3 vs. 2; P = 0.02) balloon dilations than moderate strictures.Conclusion Most patients with ER defects ≥ 90 % of luminal circumference developed strictures, many of which were severe and required early balloon dilation. There was minimal risk with ER defects < 60 %.